Contact Dermatitis in Northeast Italy Mechanics (1996–2016). Issue 2 (March 2019) - Larese Filon, Francesca; Delneri, Annalisa; Rui, Francesca; Bovenzi, Massimo; Mauro, Marcella
Abstract : Background: Mechanics are at higher risk to develop occupational skin diseases from exposure to irritants, oils, greases, preservatives, and metals. Aims: The aim of the study was to investigate contact dermatitis in mechanics who underwent patch test in Northeastern Italy and compare them with white-collar workers (WCW). Subjects and Methods: From 1996 to 2016, 27, 381 patients with suspected allergic contact dermatitis were patch tested in Northeastern Italy; in this group, 1270 mechanics were studied. Odds ratios (ORs) and 95% confidence interval (CI), adjusted by age and sex, were calculated assuming WCW as the reference category (n = 6933). Results: Mechanics represented 4.6% of the population tested. Their mean ± SD age was 36.1 ± 11.2 years. Compared with WCW, they were found to have an increased risk of occupational dermatitis (OR = 14.4; 95% CI = 11.6–18) and hand/forearm dermatitis (OR = 2.5; 95% CI = 2.3–2.9). They presented an increased risk of sensitization to epoxy resin (OR = 2.7; 95% CI = 1.5–4.8), to thiurams (OR = 2.4; 95% CI = 1.5–3.8), to 2-mercaptobenzothiazole (OR = 1.9; 95% CI = 1.1–3.4), and to diaminodiphenylmethane (OR = 1.7; 95% CI = 1.1–2.5). Conclusions: Compared to WCW, mechanics were found to be at higher risk to develop occupational contact dermatitis, associated mainly to sensitization to epoxy resin and rubber accelerators.